Freqüência de genótipos do vírus da hepatite C em doadores de sangue atendidos no ambulatório do Núcleo de Medicina Tropical de Belém - DAMASCENO, Marcos Nazareno Rodrigues (2022)
The hepatitis C is a serious problem of public health, being considered that 3% of the world population are infected. It is caused by virus RNA that possesses a variability genetic genotypes notable and distributed subtypes in a peculiar way for the whole globe, such a genetic diversity has been reason study in what for it concerns the possible influence in the transmission, pathogenesis and answer to the treatment. With the intention of contributing for a better knowledge of the genotypes’s Hepatite C Virus (HCV) and your clinical-epidemic implications, it was aimed at mainly to determine the frequency of these genotypes in pré donors of blood bearers of HCV, triados for the Foundation HEMOPA and in accompaniment in the clinic of the Nucleus of Tropical Medicine of UFPA. They were appraised 50 patients through research protocol, and they were genotipados 28 patient until the elaboration of this work. The result was the following: 25 patient (89,3%) of the genotype type 1 three patient (10,7%) of the genotype type 3. As our work was limited relatively to the analysis of a number small of individuals (n = 28), it is done necessary to enlarge the study population in order to obtain more trustworthy values with relationship to the frequency of genotypes of HCV and your relationship with the aspects that orientate this fascinating pathology among the pré donors of blood.